The Influence of Storytelling on Students’ Confidence in Speaking English : Out of The Class Context - Mawaddah, Sakina; Maulina, Maulina; Rusli, Tri Indah (Journal of English Language and Education, 2025)
Speaking ability is an essential skill in learning English as a Foreign Language (EFL), set many students still struggle to express themselves due to a lack of confidence and speaking anxiety. Although various studies have examined storytelling techniques as a learning strategy to improve speaking skills, most have focused on classroom contexts and have not specifically explored how storytelling competitions impact students’ confidence and speaking anxiety outside the classroom. This study aims to investigate how participation in storytelling competitions can influence students’ confidence in speaking English, reduce speaking anxiety, and identify the factors that affect students’ confidence after participating in such competition. This research uses a qualitative descriptive approach with semi-structured interview and documentation methods. The subjects of the study are three junior high school students who actively participate in storytelling competitions. The data were analyzed using thematic analysis techniques based on the six phases proposed by Braun and Clarke (2006). The findings demonstrate that self-confidence develops through four main sources of self-efficacy proposed by Bandura (1977). First, mastery experience emerged as the strongest factor, where repeated participation gradually reduced students’ nervousness and built their belief in their ability to perform. Second, vicarious experience from observing peers provided both motivation and learning opportunities that encouraged self-improvement. Third, verbal persuasion in the form of support and appreciation from teachers, parents, and peers played a crucial role in strengthening students’ confidence. Finally, although students initially experienced nervousness and anxiety, these feelings transformed into pride and satisfaction after performing, showing the importance of emotional regulation in public speaking. Overall, storytelling competitions not only reduce students’ speaking anxiety but also enhance their confidence, fluency, and readiness to use English in real communication contexts.